Co-movement of output and price in Malaysia: empirical evidence and macroeconomic policy implications - Kassim, Salina; Abdul Manap, Turkhan Ali (2010)
The relationship between major economic variables provides important information in strategizing macroeconomic stabilization policy for an economy. In this study, we focus on the relationship between output and price and draw important policy implications for macroeconomic stabilization policy in Malaysia. The nature of output-price relationship provides the information about the dominant component that drives the economy’s business cycles. An economy that is characterized by a positive relation between output and price suggests the dominance of the demand shocks in influencing the macroeconomic fluctuations. In contrast, an economy where output varies negatively with price indicates the dominance of supply shocks, suggesting that the production side of the economy is influencing the economic cycles. This study conducts a comprehensive analysis of the output-price relationship in Malaysia with the objective of drawing relevant policy recommendations for effective macroeconomic stabilization policy. We analyze the short- and long-run co-movements between real activity and prices using several tests in efforts to arrive at conclusive findings. Apart from the descriptive analysis, the study relies on the VAR forecast errors based on Den Haan and Sumner (2000). The study considers an extended data sample of monthly frequency covering the period from January 1971 to November 2009. By identifying the major source of macroeconomic fluctuations in Malaysia, the study aims to contribute towards enriching policy recommendations for effective macroeconomic stabilization policy in the country.